(untitled) (Journal of Nepal Geological Society, 2015)
Nepal is considered as one of the earthquake-prone countries in the region. Earthquake is a major concern of Nepal because of rapid population growth, poor land use planning, precarious settlement patterns, and poorly implemented building code. Earthquakes in Nepal have been reported since 1255 while major earthquakes were recorded in 1408, 1681, 1810, 1833, and 1866, 1934, 1980, 1988, 2011, and 2015. An earthquake in September 18, 2011 measuring 6.9 in Richter scale, killed 6 people and injured 30 people in Nepal. There were many roadside slope damages near the epicenter area. To assess the roadside slope damages after this earthquake, a field visit was conducted and a landslide inventory map along the roadside slope was prepared for most damaged area. This paper provides a comprehensive information about earthquake-induced slope failures occurred in the Mechi Highway of eastern Nepal and also discusses an approach of earthquake-induced slope failures hazard mapping in Nepal.